Politicians and bureaucrats in Bangladesh's policy-making process a re-interpretation - Ahmed, Nizam U. (Philippine Journal of Public Administration, 1994)
Having descended from the Indian Civil Service, particularly its higher bureaucracy, the modern bureaucracy in Bangladesh is essentially a British legacy. During the Ayub regime (1958-1969) the administrative class dominated the policymaking process in order to promote economic development and unity in the country. This, however, resulted in the weakening of the policymaking process. Under the Mujib regime (1972-1975), the bureaucratic had to succumb to the pressures of the ruling elite and the civil service suffered from low morale and apathy. The bureaucracy achieved representation in various policymaking institutions like the Cabinet, the Planning Commission and the National Economic Council during the Zia regime (1977-1981). While Ayub's scorn for political parties and party politicians was highly discernible, the Zia government revived the political process and recognized the role of the party in the political system.